The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jcin.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Is Bare-Metal Stent Implantation Still Justifiable in High Bleeding Risk Patients Undergoing Percutaneous Coronary Intervention?

Abstract: Among HBR patients with stable or unstable coronary artery disease, E-ZES implantation provides superior efficacy and safety as compared with conventional BMS. (Zotarolimus-Eluting Endeavor Sprint Stent in Uncertain DES Candidates [ZEUS]; NCT01385319).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 27 publications
(10 reference statements)
6
111
4
1
Order By: Relevance
“…First, data from the DAPT trial indicate a similar impact of prolonged DAPT administration irrespective of stent type (BMS vs. DES), 128 and the risk of adverse events among patients with DAPT cessation and patients undergoing non-cardiac surgery indicate no differences between BMS and DES. 17,129,203 Second, two randomized trials have demonstrated the superiority of newer-generation DES over BMS in high bleeding risk patients who cannot tolerate long-term exposure to DAPT, 130,204 such as those needing chronic OAC (section 2.2).…”
Section: Type Of Stentmentioning
confidence: 99%
“…First, data from the DAPT trial indicate a similar impact of prolonged DAPT administration irrespective of stent type (BMS vs. DES), 128 and the risk of adverse events among patients with DAPT cessation and patients undergoing non-cardiac surgery indicate no differences between BMS and DES. 17,129,203 Second, two randomized trials have demonstrated the superiority of newer-generation DES over BMS in high bleeding risk patients who cannot tolerate long-term exposure to DAPT, 130,204 such as those needing chronic OAC (section 2.2).…”
Section: Type Of Stentmentioning
confidence: 99%
“…Figure summarizes the results of literature search. Three randomized controlled studies met the inclusion criteria; ZEUS‐HBR, LEADERS FREE, and SENIOR trials . Original ZEUS trial included patients with HBR as well patients who are deemed to be uncertain candidates either due to high thrombotic or low restenosis risk .…”
Section: Resultsmentioning
confidence: 99%
“…However, significant proportion of patients with high bleeding risk (HBR) continue to receive BMS during PCI given the perceived fear of bleeding with longer dual antiplatelet therapy (DAPT) or ST resulting from premature discontinuation of DAPT in patients receiving DES . Recently, DES with shorter DAPT has been shown to be more efficacious compared to BMS in reducing major adverse cardiovascular events (MACEs); particularly TLR . However, the results of these trials were highly variable in‐terms of reduction of ST with DES.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, the recognition that shorter courses of DAPT (3‐6 months) with second generation DES are likely safe, combined with evidence of a safety advantage for NOAC‐based antithrombotic regimens is likely largely responsible for this observed change in stent choice. Additionally, recent studies among patients at high risk for bleeding, including those requiring OAC, have demonstrated the superior efficacy and safety of using certain DES platforms compared to BMS when shorter courses of DAPT are necessary . Avoidance of restenosis with the use of DES may also help reduce the risk of bleeding complications by avoiding repeat procedures in a typically fragile AF population …”
Section: Discussionmentioning
confidence: 99%